Fatigue Through Sleep Time On Night Service Nurses At Kendari City Hospital - Prasetya, Fikki; Siji, Amalya Febriyani; Al Asyary, Al Asyary (Al-Sihah: The Public Health Science Journal, 2021)
Sleep time is the sleep time needed by nurses as a fulfillment before doing the night shift and sleeping time during the night shift to optimize work productivity to minimize work fatigue. This study aims to determine the relationship between nurses' slept time before and during shifts, slept debt, and shift rotation with fatigue on night shift nurses in the Critical Room of the Kendari City General Hospital in 2020. An analytical survey was conducted with a cross-sectional study. The results showed that there was no relationship between sleep time before the night shift and work fatigue on the night watch nurse (p-value = 0.309), in contrast to sleep time during the night shift, it was found that there was a relationship with work fatigue on the night watch nurse (p-value = 0.003 ). It is recommended that hospital management make standard operating procedures that aim to regulate nurses' sleep time during the night shift to meet their needs and reduce fatigue levels.